Natural ageing clustering under different quenching conditions in an Al-Mg-Si alloy. (1st January 2021) - Yang, Zi; Jiang, Xiaohe; Zhang, Xingpu; Liu, Meng; Liang, Zeqin; Leyvraz, David; Banhart, John
Abstract: During quenching of aluminium alloys from the solutionising temperature vacancies are partially conserved as excess vacancies, partially lost to vacancy sinks, the exact fractions depending on the cooling rate. Positron lifetime measurements in samples from interrupted quenching experiments reveal that vacancies are lost during cooling down to 200 °C, after which solute atoms start to form clusters down to 20 °C. Slow cooling leads to 1 to 2 orders of magnitude lower excess vacancies than fast cooling. Since quenched-in vacancies are crucial for natural ageing (NA) in Al-Mg-Si alloys it is surprising to find just small differences between the NA hardening kinetics after different quenches. Specifically, hardening rates differ only in the initial stage (<100 min), after which they are almost identical for NA up to ~1 year. This suggests that interactions between vacancies and early-stage solute clusters help equalising the free vacancy fractions in differently quenched samples. Graphical abstract: Image, graphical abstract